Protocol for Detection, Prevention and Action in Alleged Cases of Gender-based Violence and Discrimination - Yamila Ramos Rangel; Marianela Fonseca Fernández; Laura Magda López Angulo; Anais Marta Valladares González; Arelys Falcón Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
A protocol is presented to prevent, avoid and act in situations of gender-based violence at the University of Medical Sciences of Cienfuegos. This protocol establishes the necessary measures to identify situations of violence that occur in the university environment, whether towards students or teachers, with the aim of investigating them, proposing solutions and mitigating their consequences. The methodological and scientific rigor of the design presented allows us to offer the university community a very useful protocol that is in accordance with the Comprehensive Strategy for Prevention and Attention to Gender Violence and Violence in the Family Setting and the Advancement Plan to Women that is implemented in Cuba.